Tinjauan Kapasitas Sistem Drainase di Perumahan Center Park Palembang Menggunakan PCSWMM - Al Amin, M. Baitullah; Haki, Helmi; Alia, Febrinasti (Jurnal Rekayasa Sipil (JRS-Unand), 2022)
This research focuses on reviewing the drainage system's capacity in Alang-Alang Lebar Center Park Residential Area, Palembang City. Several spots in this area are frequently flooded, especially during heavy rainfall. Field surveys were conducted to acquire the required data, such as topographic maps, aerial photographs, dimensions, and elevations of drainage channels. This research uses the maximum daily rainfall data recorded at the Sultan Mahmud Badaruddin II Airport station for 25 years (1996 – 2020). The return periods used to determine the magnitude of 3 hours-design rainfall are 2 and 5 years. The hydrodynamic simulation of the drainage system was carried out with an integrated 1D-2D model using PCSWMM 2021 Professional 2D version 7.4. The simulation results show flooding occurred in the Willow, Cassia, Bougenville, and Amaryllis blocks. The most significant overflow occurred in the Willow block, causing flood inundation with a maximum height of 0.1 m. Recommendations for increasing the capacity of the drainage system to prevent flood overflows are by enlarging several secondary channels and adding culverts to divert some of the flow discharge in a channel so that it is distributed to other channels. The results of this study are expected to confirm the capability of the PCSWMM model in the design and evaluation of drainage systems in urban areas. Also, the results of this study are expected to emphasize the importance of the role of the hydrodynamic model as a tool for planning the capacity of an adequate drainage system.